Sharing Time Learning (Face to Face and Online Learning) in Blended Learning - Mulyani Azis, Yunia; Suharyati, Henny; Susanti, Sussy (International Journal of Psychosocial Rehabilitation, 2020)
Blended learning is a combination of learning face to face (f2f) with online learning, because it is a merger of two methods, automatically a teacher should be able to devote time to both of the learning method to increase learning outcomes. This research was conducted with the aim to (1) seek timely manner between the percentage of blended learning and face to face (f2f) in order to achieve an increase in maximum learning results and (2) look at the effectiveness of blended learning. Research method that being used is experimental method performed using 2 different percentage of instructional time. Class A and B using the percentage of time 60% online learning and 40% f2f, while class C and Dusing the percentage of time 75% online learning and 25% f2f. Conclusions of this study were (1) lecture and students agree with blended learning teaching methods and stated that this method is quite effective, (2) the composition of the time yet to get the learning outcomes as expected, but the learning outcomes of students studying with the composition 60% online and 40% f2f slightly better than students who studied the composition of the time 75% online and 25%f2f